Lesiones pruriginosas violáceas en gestante de 18 años de edad con embarazo de 23 semanas de gestación - Ramirez Olvera, Shirley Amada (2018)
This is a pregnant woman of 18 years of age with 23 weeks of gestation, without prenatal control and characterized by three months of appearance of violaceous spots in the perineal region and of the vulva (major and minor lips), whose objective was the "Determine characteristics of violaceous pruritic lesions at the level of the vulva with pregnancy of 23 weeks of gestation "and evaluate the situations that affect the health of pregnant women suffering from syphilis. A previous anamnesis was made with gynecological-obstetric, personal data, highlighting no prenatal control and controlled hypertension with losartan of 29mg, and the presence of pruritic lesions in the bulbar region of the major and minor lips, physical examination without problems and with definitive diagnosis: Pregnancy of 23 weeks of gestation plus secondary syphilis, with the presence of pruritic lesions of the major and minor bulbar arteries. High-risk pregnancy ICD 10 Z35.- One dose of 2.4.million penicillin benzathine, intramuscular, was administered in emergency. It was applied in the lesions at the level of the rose hip vulva to relieve the itching. The test called Campo Oscuro was sent to the laboratory